2020
DOI: 10.1101/2020.08.03.235028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CSDE1 is a Post-Transcriptional Regulator of the LDL Receptor

Abstract: In humans, clearance of LDL cholesterol, which causes atherosclerotic heart disease, is mediated by the hepatic LDL receptor (LDLR). As a result, therapies that upregulate the LDLR are highly effective treatments for atherosclerosis. Since cardiovascular disease remains the leading cause of death in Western countries, we sought to identify regulators of the LDLR beyond the known genetic causes of familial hypercholesterolemia. Here we show that CSDE1, an RNA-binding protein involved in mRNA stability, enhan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
(158 reference statements)
0
4
0
Order By: Relevance
“… 22 Altogether, the four screens identify a total of 490 genes whose knockout alters LDL-C uptake under either SER or SS conditions (299 decrease uptake, 180 increase uptake, 11 do both at FDR <0.1; Figure 1 F; Table S2 ), increasing the number of such genes compared with previously published screens. 21 , 22 , 33 , 34 We observed a positive correlation in the gene-level phenotype across our screens (R = 0.36–0.53 for 229 union gene set; Figure S1 F). We find robust but incomplete correlation in the gene-level log2 fold change in screens of SER vs. SS conditions (R = 0.43 for 1,800 genes in KO-Library 3; Figure S1 G) and in our HepG2 SS screens vs. previous screens in SS HuH7 cells (R = 0.50 for 203 genes in KO-Library 4; Figure S1 H), suggesting that environmental conditions and cell line influence the genetic control of LDL-C uptake.…”
Section: Resultsmentioning
confidence: 77%
“… 22 Altogether, the four screens identify a total of 490 genes whose knockout alters LDL-C uptake under either SER or SS conditions (299 decrease uptake, 180 increase uptake, 11 do both at FDR <0.1; Figure 1 F; Table S2 ), increasing the number of such genes compared with previously published screens. 21 , 22 , 33 , 34 We observed a positive correlation in the gene-level phenotype across our screens (R = 0.36–0.53 for 229 union gene set; Figure S1 F). We find robust but incomplete correlation in the gene-level log2 fold change in screens of SER vs. SS conditions (R = 0.43 for 1,800 genes in KO-Library 3; Figure S1 G) and in our HepG2 SS screens vs. previous screens in SS HuH7 cells (R = 0.50 for 203 genes in KO-Library 4; Figure S1 H), suggesting that environmental conditions and cell line influence the genetic control of LDL-C uptake.…”
Section: Resultsmentioning
confidence: 77%
“…The final library (KO-Library 4) contains four gRNAs targeting 522 genes with significant or near-significant effects on LDL-C uptake from the three previous screens as well as from a recently published genome-wide LDL-C uptake CRISPR-Cas9 screen performed in Huh7 cells 23 . Altogether, the four screens identify a total of 490 genes whose knockout significantly alters LDL-C uptake in either SER or SS conditions (299 decrease uptake, 180 increase uptake, 11 do both at FDR <0.1, Figure 1F, Supplemental Table 2), substantially increasing the number of such genes as compared to previous published screens 22,23,34,35 . We observe a positive correlation in the gene-level phenotype across our screens (R=0.36-0.53 for 229 union gene set, Figure S1F).…”
Section: Genome-scale Crispr-cas9-nuclease Screening Identifies Hepat...mentioning
confidence: 89%
“…Additional transcription factors have been identified that modify LDLR expression through sterol-independent mechanisms [28][29][30]. Unbiased genome-wide CRISPR screens by our group and others have identified other transcriptional regulators whose perturbation influences LDL uptake or LDLR abundance [7,31].…”
Section: Discussionmentioning
confidence: 99%